Principles for Digital Development (digitalprinciples.org, 2018)
The Principles for Digital Development serve as a compass for those wo rking to promote sustainable and inclusive development in today’s comp lex digital landscape. Using these Principles as a starting point, pol icymakers, practitioners, and technologists will be better equipped to ensure that all people can benefit from digital initiatives and from the broader digital society. Originally developed in 2014, the Princip les are officially endorsed by more than 300 organizations, including donors, international organizations, and civil society organizations. During the first decade (2014-2024), they widely influenced funder pro curement policies and the design and implementation of development pro grams. In 2024, the Principles were updated in consultation with a div erse set of individuals and organizations. Through this effort, the co mmunity expressed the need for the Principles to better reflect that p eople today largely interact with technology outside of development pr ograms. Today, all people – even those who do not yet have access to o r use technology – live in societies that are increasingly shaped by d igital ecosystems that can bring both immense benefit and immense harm . Therefore, the refreshed Principles recognize the need for radical i nclusion and local ownership; elevate issues arising from the generati on and use of digital data; and intentionally speak to the original au dience while resonating further with the full diversity of individuals and organizations that exert power over the design, deployment, and g overnance of digital systems and solutions. The Principles are mutuall y reinforcing, as they emphasize the actions needed to ensure no one i s left behind in an increasingly digital world.